The Effect of Self-Efficacy, Socioeconomic Parents, and Job Expectations on Interest in Continuing Masters Studies - Krisdayanti, Witri; Rosy, Brillian (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2023)
The study aimed to see the effect of self-efficacy, socioeconomic parents, and job expectations on the interest in continuing master's studies in Office Administration Education students at Surabaya State University. The study used a quantitative method of associative approach. Research data were obtained by distributing questionnaires via google form. The research subjects were 55 undergraduate student populations of Office Administration Education Study Program at Surabaya State University Class of 2019. Using the total sampling form, all members of the population were determined as research samples. Instrument construction testing uses validity and reliability tests, while data analysis uses classical assumption tests, multiple linear regression analysis, and hypothesis testing assisted by IBM SPSS 23. The research findings show that partially there is a positive and simultaneously significant effect of the variables of self-efficacy, socioeconomic parents, and job expectations on the interest in continuing master's studies in Surabaya State University Office Administration Education students.